Imaging the Injured Lung: Mechanisms of Action and Clinical Use. (September 2019) - Cereda, Maurizio; Xin, Yi; Goffi, Alberto; Herrmann, Jacob; Kaczka, David W.; Kavanagh, Brian P.; Perchiazzi, Gaetano; Yoshida, Takeshi; Rizi, Rahim R.
Abstract : Acute respiratory distress syndrome (ARDS) consists of acute hypoxemic respiratory failure characterized by massive and heterogeneously distributed loss of lung aeration caused by diffuse inflammation and edema present in interstitial and alveolar spaces. It is defined by consensus criteria, which include diffuse infiltrates on chest imaging—either plain radiography or computed tomography. This review will summarize how imaging sciences can inform modern respiratory management of ARDS and continue to increase the understanding of the acutely injured lung. This review also describes newer imaging methodologies that are likely to inform future clinical decision-making and potentially improve outcome. For each imaging modality, this review systematically describes the underlying principles, technology involved, measurements obtained, insights gained by the technique, emerging approaches, limitations, and future developments. Finally, integrated approaches are considered whereby multimodal imaging may impact management of ARDS. Abstract : Pulmonary imaging provides major insights into the pathophysiology of lung injury and informs current respiratory care. Integrated approaches to conventional and advanced imaging, including bedside techniques, will continue to advance management of the injured lung.Supplemental Digital Content is available in the text.